Cost analysis of dalbavancin versus standard of care for the treatment of acute bacterial skin and skin structure infections (ABSSSIs) in two Italian hospitals. Issue 2 (19th April 2023) - Bai, Francesca; Mazzitelli, Maria; Silvola, Sofia; Raumer, Francesca; Restelli, Umberto; Croce, Davide; Marchetti, Giulia; Cattelan, Anna Maria
Abstract: Objectives: Thanks to its long half-life, dalbavancin qualifies as an optimal drug for saving costs. We aimed to assess the cost and effectiveness of dalbavancin versus the standard of care (SoC). Patients and methods: We conducted a multicentre retrospective study, including all hospitalized or outpatients diagnosed with ABSSSIs at Padua University Hospital, Padua and San Paolo Hospital, Milan (1 January 2016 to 31 July 2020). We compared patients according to antibiotic treatment (dalbavancin versus SoC), the number of lines of dalbavancin treatment, and monotherapy or combination (dalbavancin in association with other antibiotics). Primary endpoints were direct medical costs and length of hospital stay (LOS) associated with ABSSSI management; Student's t -test, chi-squared test and one-way ANOVA were used. Results: One hundred and twenty-six of 228 (55.3%) patients received SoC, while 102/228 (44.7%) received dalbavancin. Twenty-seven of the 102 (26.5%) patients received dalbavancin as first-line treatment, 46 (45.1%) as second-line, and 29 (28.4%) as third- or higher-line treatment. Most patients received dalbavancin as monotherapy (62/102; 60.8%). Compared with SoC, dalbavancin was associated with a significant reduction of LOS (5 ± 7.47 days for dalbavancin, 9.2 ± 5.59 days for SoC; P < 0.00001) and with lower mean direct medical costs (3470 ± 2768€ for dalbavancin; 3493 ± 1901€ for SoC; P = 0.9401). LOS was also reduced for first-line dalbavancin, in comparison with second-, third- or higher-line groups, and for dalbavancin monotherapy versus combination therapy. Mean direct medical costs were significantly lower in first-line dalbavancin compared with higher lines, but no cost difference was observed between monotherapy and combination therapy. Conclusions: Monotherapy with first-line dalbavancin was confirmed as a promising strategy for ABSSSIs in real-life settings, thanks to its property in reducing LOS and saving direct medical costs.